File Encryption and Decryption using AES and RSA Algorithm - Manasvi Malhar Sudershan; Sai Varshan Pydakula; Aarthi Priya R (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2023)
In the present scenario, no technology that's connected to the internet is unhackable. All digital services like internet communication, military and medical imaging systems, multimedia systems require reliable security in storage and transmission of digital images. The importance of protecting digital images cannot be overstated. Therefore, there is a need for image encryption techniques in order to hide images from such attacks. In this encryption process, we use AES and RSA Algorithm in order to hide images. This encryption techniques helps us to avoid intrusive attacks. Since, the image is encrypted using the AES technique, only the receiver can view it, as the key is known only to the sender and receiver. Overall, image encryption improves data integrity and can raise consumer trust.